An analysis of outlaw motorcycle gang crime: are bikers organised criminals?. Issue 2 (3rd April 2019) - Lauchs, Mark; Staines, Zoe
ABSTRACT: Outlaw motorcycle gangs (OMCGs) are identified in Australia and internationally as being heavily involved in organised crime and/or as being criminal organisations. However, academic studies have shown that OMCG members are involved in organised crime to varying extents; this differs between clubs and across jurisdictions. To date, Australian studies of OMCGs are rare. Despite this, Australian governments target OMCGs as key players in organised crime. This study contributes to the existing literature by analysing OMCGs' criminality in one Australian jurisdiction – Queensland. It draws on rich qualitative data to determine whether and to what extent Queensland's OMCGs are involved in serious crime, organised crime and/or are operating as criminal organisations. The study finds that Queensland's OMCG members participate in serious crime at a higher rate than the general public, but that there are few examples of organised crime. There is little to no evidence of OMCGs acting as criminal organisations.